Water Sorption Properties and Hydrothermal Stability of Al-Containing Metal–Organic Frameworks CAU-10 and MIL-96 Studied Using Quasi-Equilibrated Thermodesorption - Waclaw Makowski; Patrycja Gryta; Gabriela Jajko-Liberka; Monika Cieślik-Górna; Aleksandra Korzeniowska (Molecules)
A novel experimental technique, quasi-equilibrated temperature-programmed desorption and adsorption (QE-TPDA), was used to study the water sorption properties and hydrothermal stability of aluminum trimesate MIL-96 and aluminum isophthalate CAU-10, which have been selected due to their remarkable sorption properties. The QE-TPDA profiles of water observed for MIL-96 and CAU-10 confirmed the hydrophilic nature of these materials. Complex QE-TPDA profiles indicate that water sorption in MIL-96 follows a three-step pore filling mechanism. The shape of single desorption peaks in the QE-TPDA profiles for CAU-10 confirms that water sorption involves a reversible phase transition. Based on the QE-TPDA profiles, the water adsorption heat was determined: 45–46 kJ/mol for CAU-10 and 43–56 kJ/mol for MIL-96, in the latter case depending on the adsorption extent. Hydrothermal stability tests revealed that MIL-96 retained its stable porosity-related sorption capacity for water after hydrothermal treatment up to 290 °C. Gradual changes in the QE-TPDA profiles due to the hydrothermal treatment above 290 °C, with decreasing the high-temperature desorption peak and increasing the low-temperature one, indicate minor structural changes occurring in this material. Only after 410 °C treatment was fast degradation of MIL-96 observed. CAU-10 exhibited high and unchanged hydrothermal stability up to 400 °C.